Vietnamese EFL Teachers’ Perceptions and Practices of Reflective Teaching as a Tool for Professional Development - Tuan, Duong Minh (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
Growing professionally is considered a crucial goal that language teachers may wish to achieve in their teaching careers. Although tools for professional development can be varied in different contexts, reflective teaching as an essential and ongoing job is likely to be among the most common ones. The contributions of reflection on pursuing teacher professional development have been proved in numerous studies. However, research on the views and implementation of such a tool by EFL teachers in the Vietnamese context is insufficient. To narrow this gap, this descriptive study was conducted to investigate Vietnamese EFL teachers’ perceptions and practices of reflective teaching as a tool for teacher professional development. A mixed-methods design was employed to collect both quantitative and qualitative data for the study. Specifically, quantitative data were obtained through a questionnaire, and qualitative data were attained using a semi-structured interview. As regards participants, twenty-five university EFL teachers in the Mekong Delta of Vietnam participated in this study. The results indicated that the participants held positive perceptions towards reflective teaching and perceived it to be “very significant” to teacher professional development. Nevertheless, it was found that their overall level of reflective practices was identified as “average”. By comparison, a statistically significant difference between the participants’ perceptions and practices of reflective teaching was observed. The results also showed that the participants’ strategies of reflecting on their teaching practices were not diverse, with sharing classroom experiences with colleagues and conducting peer observation being the popularly used ones.